A bidirectional and low-frequency energy harvester for collecting human crowd energy in shopping malls. (15th January 2022) - Ren, Limin; Luo, Yu; Lu, Guangpeng; Cong, Moyue; Wang, Xinyu; Wang, Kuankuan; Guo, Zhanchen; Tan, Yisong
Graphical abstract: Abstract: Human crowd kinetic energy is a promising electricity source in shopping malls. Harvesting human crowd energy can supply considerable power for lighting and door control. In this study, a bidirectional low-frequency energy harvester was proposed, analysed, fabricated, and tested. The harvester was mainly composed of a hinge, four one-way bearings, one sun gear, one internal gear, one planetary gearbox and one direct current motor. The hinge was used to connect the door. The combination of these one-way bearings, hollow shaft, solid shaft and gears transformed the bidirectional movement into unidirectional movement. The utilization of the planetary gearbox boosted the velocity of the door movement to overcome the low-frequency problems. The motor generated a varied direct current voltage. A theoretical analysis was performed to ascertain the factors that would determine the energy harvester's performance. A full-size prototype was fabricated, a simulated shopping door environment was created, and experiments were investigated. The simulation results correlated well with the experimental results. At an ultralow door movement (45°/s), the harvester can output an open-circuit voltage of 7.4 V (steady voltage) and a power of 3046 mW. The harvester had a high efficiency up to 56.79%. The harvested voltage can power electronic locks, LED billboards and wireless doorbells, all of which are necessary apparatuses in shopping malls. The proposed harvester can potentially be used in shopping malls to harvest plentiful human crowd kinetic energy.